Impact of smoking behavior on clozapine blood levels – a systematic review and meta‐analysis. (27th September 2020) - Wagner, E.; McMahon, L.; Falkai, P.; Hasan, A.; Siskind, D.
Abstract : Objective: Tobacco smoking significantly impacts clozapine blood levels and has substantial implications on individual efficacy and safety outcomes. By investigating differences in clozapine blood levels in smoking and non‐smoking patients on clozapine, we aim to provide guidance for clinicians how to adjust clozapine levels for patients on clozapine who change their smoking habits. Methods: We conducted a meta‐analysis on clozapine blood levels, norclozapine levels, norclozapine/clozapine ratios, and concentration to dose (C/D) ratios in smokers and non‐smokers on clozapine. Data were meta‐analyzed using a random‐effects model with sensitivity analyses on dose, ethnic origin, and study quality. Results: Data from 23 studies were included in this meta‐analysis with 21 investigating differences between clozapine blood levels of smokers and non‐smokers. In total, data from 7125 samples were included for the primary outcome (clozapine blood levels in ng/ml) in this meta‐analysis. A meta‐analysis of all between‐subject studies ( N  = 16) found that clozapine blood levels were significantly lower in smokers compared with non‐smokers (Standard Mean Difference (SMD) −0.39, 95% confidence interval (CI) −0.55 to −0.22, P  < 0.001, I 2  = 80%). With regard to the secondary outcome, C/D ratios ( N  = 16 studies) were significantly lower in the smoker group ( n  = 645) compared with the non‐smoker group ( n  = 813; SMD −0.70, 95%CI −0.84 to −0.56, P  < 0.00001, I 2  = 17%). Conclusion: Smoking behavior and any change in smoking behavior is associated with a substantial effect on clozapine blood levels. Reductions of clozapine dose of 30% are recommended when a patient on clozapine stops smoking. Reductions should be informed by clozapine steady‐state trough levels and a close clinical risk‐benefit evaluation.